2011
DOI: 10.3141/2231-13
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impacts of Information and Communication Technologies and Virtual Activities on Activity and Travel Behavior

Abstract: The boom in telecommunications is expected to have many impacts on peoples' activities and travel behavior. Recent advances in information and communication technologies (ICTs) make it possible to conduct activities virtually. Thus the need for physical travel for some types of activities is obviated. Accordingly, the use of ICT may contribute to reducing urban congestion and alleviating air quality problems. However, ICT may generate significant additional travel because of the increased connectivity and acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…SEMs enable analysts to predict multiple endogenous variables in a simultaneous manner and also allow for incorporating latent factors into the model (68). SEMs have been widely used in capturing direct and indirect causal effects in a variety of behavioral studies (36,37,(69)(70)(71)(72)(73)(74)(75)(76). A sample path diagram demonstrating potential causal relationships is presented in Figure 9.…”
Section: Methodology and Model Structurementioning
confidence: 99%
“…SEMs enable analysts to predict multiple endogenous variables in a simultaneous manner and also allow for incorporating latent factors into the model (68). SEMs have been widely used in capturing direct and indirect causal effects in a variety of behavioral studies (36,37,(69)(70)(71)(72)(73)(74)(75)(76). A sample path diagram demonstrating potential causal relationships is presented in Figure 9.…”
Section: Methodology and Model Structurementioning
confidence: 99%
“…Second, they allow the analyst to incorporate latent factors into the model (Bollen, 1989 ). The literature documents successful application of structural equation models in a variety of behavioral studies (Asgari et al, 2016 ; Asgari & Jin, 2017 , 2019 ; Cao, 2016 ; De Vos et al, 2021 ; Etminani-Ghasrodashti & Ardeshiri, 2015 ; Ingvardson & Nielsen, 2019 ; Lavieri et al, 2017 ; Mosa, 2011 ). SEM analysis is usually accompanied by a graphical manifestation, referred to as the “path diagram”.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, people substituted home teleshopping time for shopping travel time, and teleshoppers took fewer shopping trips and traveled shorter distances for shopping purposes (45). Mosa (2011) showed that there are direct feedback effects between the use of information and communication technologies and in-home and out-of-home nonmandatory activities (46). Using data from the 2009 National Household Travel Survey, Zhou and Wang (2014) explored the bidirectional connection between online shopping and in-store shopping.…”
Section: Literature Reviewmentioning
confidence: 99%